MODELO CONSTRUCTIVISTA Y SU INCIDENCIA EN EL APRENDIZAJE DE ESTUDIANTES CON NEE DE LOS ESTUDIANTES DE 5TO AÑO DE EDUCACIÓN BÁSICA DE LA ESCUELA RAFAEL MORÁN VALVERDE PERIODO LECTIVO 2024-2025 - RAMÍREZ MONTERO YUTSETH KATHERINE (2024)
This case study, which responds to the theme "Constructivist model and its impact on the learning of students with SEN of students in the 5th year of basic education of the Rafael Morán Valverde School for the 2024-2025 school year”, aims to determine the effectiveness of constructivist methodologies in the learning of students with SEN associated with reading and writing problems and mathematical skills. To this end, research with a descriptive level of depth was proposed with a mixed approach and included a semi-structured interview addressed to the teacher in charge of the 5th grade of EGB. As well as a survey applied to students of this course who had the learning disorders mentioned above. The results obtained revealed that constructivist pedagogical strategies have a very considerable level of effectiveness in students who presented this type of learning difficulties, especially when the teacher has applied the key principles of this educational model and identifies the main predictors that influence the development of these skills. The conclusions highlighted that constructivist activities based on playful games and the direct manipulation of teaching materials are easier for students with SEN to assimilate and apply. This allows them to build their own knowledge through the association of previous experiences with the new skills and abilities they work on in class.